2022
DOI: 10.21608/ejnf.2022.286670
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Different Levels of Clove Essential Oil on the Growth Performance, Lipid Metabolism, Immunity, and Intestinal Microbial Structure of Broiler Chickens

Abstract: his study aimed to evaluate the impact of different levels of clove essential oil (CEO) on the growth performance, cecal microbial status, and serum metabolites of broilers using it as an alternative to antibiotic growth promoters. Two hundred and fifty, one-day-old chicks of the Ross 308 strain were randomly divided into five groups, each having 50 chicks. The experimental groups were as follows: G1, a basal diet with no additive; G2, a basal diet supplemented with 20 mg/kg avilamycin; G3, G4, and G5 were sup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Clove and its extracts ( Syzygium aromaticum ) are among the most used medicinal herbs for their high content of biologically active compounds that have antimicrobial and antioxidant properties. Moreover, it stimulates growth, immunity, and hypochelesterolemic activities 14 , which is due to its antimicrobial, antioxidant, and digestive properties 13 . We hypothesized that clove essential oils and probiotics combined might alleviate the adverse effects of heat stress on growth performance, by enhancing immuno-antioxidant status, and intestinal health.…”
Section: Introductionmentioning
confidence: 99%
“…Clove and its extracts ( Syzygium aromaticum ) are among the most used medicinal herbs for their high content of biologically active compounds that have antimicrobial and antioxidant properties. Moreover, it stimulates growth, immunity, and hypochelesterolemic activities 14 , which is due to its antimicrobial, antioxidant, and digestive properties 13 . We hypothesized that clove essential oils and probiotics combined might alleviate the adverse effects of heat stress on growth performance, by enhancing immuno-antioxidant status, and intestinal health.…”
Section: Introductionmentioning
confidence: 99%
“…Clove (Syzygium aromaticum; family Myrtaceae) ower buds contain high amounts of volatile essential oils, with eugenol being the dominant component, in addition to other phytochemicals that account for their numerous health bene ts (Arif et al 2022). Dietary clove supplementation improves nutrient absorption and utilization, growth performance, meat yield, immunity, bene cial intestinal bacteria (Elbaz et al 2022) as well as protein digestibility, nutrient availability and utilization in broilers (Kunnumakkara et al 2018). However, negative effects on growth performance with increasing inclusion levels of clove seed (Suliman et al 2021) or clove buds (Otham et al 2022) have also been reported.…”
Section: Introductionmentioning
confidence: 99%